ChemInform Abstract: Synthesis and Surface Chemistry of High Quality Wurtzite and Kesterite Cu2ZnSnS4 Nanocrystals Using Tin(II) 2‐Ethylhexanoate as a New Tin Source. Issue 41 (October 2015) - Gabka, Grzegorz; Bujak, Piotr; Gryszel, Maciej; Ostrowski, Andrzej; Malinowska, Karolina; Zukowska, Grazyna Z.; Agnese, Fabio; Pron, Adam; Reiss, Peter
Abstract A new synthesis of the title nanocrystals is reported, in which solid and difficult to dissolve precursors of tin are replaced by liquid tin(II) 2‐ethylhexanoate.